Search for a heavy resonance decaying into a Z plus jet final state in p(p)over-bar collisions at root s=1.96 TeV using the D0 detector - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. -L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Soc, 2006)
We have searched for a heavy resonance decaying into a Z+jet final state in p (p) over bar collisions at a center of mass energy of 1.96 TeV at the Fermilab Tevatron collider using the D0 detector. No indication for such a resonance was found in a data sample corresponding to an integrated luminosity of 370 pb(-1). We set upper limits on the cross section times branching fraction for heavy resonance production at the 95% C.L. as a function of the resonance mass and width. The limits are interpreted within the framework of a specific model of excited quark production.